The paradox of the Promotion Office of the ASN through Merit System in Environment The Government Of The Province Of Central Kalimantan - Edy, Nurul (Government Studies of Muhammadiyah Malang University/AIPPTM, 2018)
Act No. 5 of the year 2014 about ASN emphasized that promotion of the incumbent should be done in a transparent, equitable and professional, as well as putting forward the competence (knowledge and skills) that employees ASN. In fact, the implementation of open selection Promotion Office of the ASN is not fully able to walk according to the desired ACT ASN. This research specifically discusses the implementation of open selection Promotion Office of the ASN by using qualitative research approaches in which researchers describe the problems occurred at each stage of the implementation of the selection Open the Promotion Office of the ASN in the provincial Government of Central Kalimantan environment. The research found there is a political intervention of the head of the region in the implementation of the selection of promotional Office ASN so determination and placement of the ASN in the Government established by the Chief of the area, not on the basis of the results of the selection by the selection team. Therefore, the design of the implementation selection Promotion Office of the ASN should be emphasized on minimizing political intervention and involvement of the regional head of ASN in the practical implementation of the promotion so that political position may be run in a professional manner.